Comparative Analysis of the Efficacy of Bacillus subtilis and Lactoba-cillus acidophilus in Inhibiting Vibrio parahaemolyticus Infection in Black Tiger Shrimp (Penaeus monodon) - Ery Gusman; Andini Aisyah Nur Raoda; Diana Maulianawati; Rukisah Rukisah; Zainuddin Zainuddin; Imra Imra (Journal of Aquaculture and Fish Health, 2026)
The application of probiotic bacteria in black tiger shrimp (Penaeus monodon) aquaculture constitutes a preventive strategy aimed at mitigating the risk of disease outbreaks. This study aims to compare the efficacy of Bacillus subtilis and Lactobacillus acidophilus in inhibiting Vibrio parahaemolyticus infection through both in vitro and in vivo evaluations. The research was conducted from January to March 2025 at the Fisheries Biology Laboratory, Faculty of Fisheries and Marine Science, Universitas Borneo Tarakan. This study used a Completely Randomized Design (CRD) with four treatments and three replicates each, namely Control (-) uninfected and without probiotics, Control (+) infected with V. parahaemolyticus at 104 CFU/mL without probiotics, Bs given B. subtilis at 108 CFU/mL and infected with V. parahaemolyticus at 104 CFU/mL, and La given L. acidophilus at 108 CFU/mL and infected with V. parahaemolyticus at 104 CFU/mL. Observed parameters included antibacterial inhibition, survival rate (SR), mortality pattern, mean time to death (MTD), relative percentage survival (RPS), bacterial population, clinical symptoms, and water quality. L. acidophilus demonstrated greater efficacy than B. subtilis in inhibiting V. parahaemolyticus infection in black tiger shrimp. The survival rate of shrimp treated with L. acidophilus reached 69.67%, whereas the group treated with B. subtilis exhibited a survival rate of 43.00%. Overall, the application of L. acidophilus consistently yielded superior survival outcomes compared to B. subtilis.